Politik Hukum Pengaturan Unsur Pimpinan Partai Politik - kuswanto kuswanto (Justicia Journal, 2015)
Political party is a precondition for democracy. Political party should receive public trust to exist as the people’s representative. Indonesian politics to day distrusts the political party. Many politicians are prosecuted because commiting criminal offense such as corruption. To respond this situasion, the dignity of the political party needs to be restored. This article proposes that requirements of political party leader should be regulated in legislation. Political party leader should have moral and ethics capability higher than its regular member. Furthermore, this article proposes that the law No 2 of 2008 should be amended to accommodate this proposal.